Detección de violencia contra la mujer en la consulta del médico de familia - García Torrecillas, Juan Manuel (Aten Primaria, 2008)
OBJECTIVES: To find out the magnitude of violence against female partners among patients who visit their family doctor.To study frequency and acceptance of its investigation by the family doctor and to assess the effectiveness of a screening question on abuse. DESIGN: Descriptive, cross-sectional study. SETTING: Primary care, 4 samples from 2 urban health centres in Jaén, Spain. PARTICIPANTS: Who participated 170 women randomly selected from the female consulting population. MEASUREMENTS: Interviews by means of the Bradley modified test and the anxiety and depression Goldberg scales. Perceived health, frequency of detection of domestic violence, by the family doctor, and female opinions were also studied. RESULTS: During the last year, abuse against women was detected in 22.9% of the female population consulting their family doctor (95% confidence interval [95% CI],16.6-29.2). Abused women had a worse perception of health (odds ratio [OR] =4.2;95% CI, 1.02-17.5) and a higher probability of depression (OR=4.7; 95% CI, 1.8-12.5) independently from the rest of variables. The question “How are the things going with your partner?” as a screening of abuse does obtain a positive probability quotient of 6.23 (95% CI, 3.6-10.9), a specificity of 89% and a negative predictive value of 90%. Of those interviewed, 96.5% would not mind if their family doctor approached the couple’s relationships, a situation that occurs in 24.7% of cases. CONCLUSIONS: Some degree of abuse was detected in almost a quarter of women who consult their family doctor. Family doctors do not usually ask about family and partner relationships and environment, although for almost all women it is well appreciated and the item has an increased likelihood ratio and high negative predictive value in detecting abuse.